2002
DOI: 10.1002/syn.10040
|View full text |Cite
|
Sign up to set email alerts
|

Kainate‐induced currents in rat cortical neurons in culture are modulated by riluzole

Abstract: The action of the neuroprotective and anticonvulsant agent riluzole on kainate-induced currents was studied in rat cortical neurons in primary culture by using the whole-cell configuration of the patch-clamp technique. Kainate elicited macroscopic, 6-cyano-7-nitroquinoxaline-2,3-dione (CNQX)-sensitive inward currents in all the patched cells and the amplitude of the current was concentration-dependent (EC50= 106 microM). Riluzole decreased the inward currents induced by 100 microM kainate at all holding potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 43 publications
0
27
0
Order By: Relevance
“…A major issue of the use of riluzole is its specificity: other studies have shown that riluzole also blocks potassium channels (Zona et al, 1998;Duprat et al, 2000;Cao et al, 2002;Ahn et al, 2005), calcium channels (Huang et al, 1997), and glutamatergic synaptic transmission (Zona et al, 2002;Albo et al, 2004). However, it is unlikely that the effects of riluzole reported here are attributable to these nonspecific effects.…”
Section: Riluzole Block Of I Na(p) In Spinal Neuronsmentioning
confidence: 63%
“…A major issue of the use of riluzole is its specificity: other studies have shown that riluzole also blocks potassium channels (Zona et al, 1998;Duprat et al, 2000;Cao et al, 2002;Ahn et al, 2005), calcium channels (Huang et al, 1997), and glutamatergic synaptic transmission (Zona et al, 2002;Albo et al, 2004). However, it is unlikely that the effects of riluzole reported here are attributable to these nonspecific effects.…”
Section: Riluzole Block Of I Na(p) In Spinal Neuronsmentioning
confidence: 63%
“…It is worth noting that miniature EPSC amplitude reduction by riluzole, although statistically significant, was small, suggesting that direct modulation of synaptically activated glutamate receptors by riluzole may be a minor contributor to reduction of synaptic transmission; in contrast, while the reduction of glutamate receptor currents by riluzole was greater, the method of application used here is more likely to activate predominantly extrasynaptic glutamate receptors (Townsend et al 2003). In addition, although some studies have reported that electrophysiological responses to glutamate receptor ligands were inhibited by riluzole (Centonze et al 1998;Debono et al 1993;Zona et al 2002), this inhibition may be via indirect modulation of receptor function, as a number of radioligand binding studies have consistently failed to find any interaction of riluzole with the NMDA, glycine, or phencyclidine binding sites of NMDA glutamate receptors or the ligand binding site of non-NMDA glutamate receptors (Benavides et al 1985;Debono et al 1993;He et al 2002).…”
mentioning
confidence: 99%
“…It has been reported that riluzole increased the time constant of fast desensitization and decreased the time constant of slow desensitization and steady-state current of GABA A and glycine receptors (5). Also, riluzole decreased the activity of AMPA receptors and the kainate-induced currents (4,7). These results indicate that riluzole inhibits neuronal excitability and protects against excitotoxicity.…”
Section: Discussionmentioning
confidence: 70%